Hubungan antara Sistem Pembelajaran Daring selama Pandemi Covid-19 dengan Tingkat Kecemasan Mahasiswa Program Khusus di STIKes Maharani Malang - NOVI DWI ESTERLINA (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Online learning is learning that is carried out using an internet-connected platform. If the implementation is not good it can cause anxiety. The design of this study used a correlative design with a cross sectional approach. The number of samples is 34 respondents. The instrument used was an online learning questionnaire and the Zung Self-Scale Anxiety Scal (SAS/SRAS) anxiety level. The data analysis method is the Spearman Correlation Test. The results of the study half (50%) of respondents said that the implementation of online learning was good. And almost all (91%) did not experience anxiety (normal) and (9%) experienced mild anxiety. The results of the Spearman Correlation Test showed the value of p = 0.028 <0.05 and the value of r = -0.376. The better the online learning is done, the lower the level of anxiety. Online learning is judged from the four indicators that it is good, it is necessary to pay attention to the factors that influence anxiety. The researcher hopes that this research can be a reference for further research with different factors, variables, locations to make it more complex.